Preparation techniques, functionalization, and cytotoxicity of magnetic nanoparticles: A review - Humaira Sultana; Afifa Shafiq; Muhammad Akram Choohan; Khalil Ahmad; Ume Habiba (AMMANIF, 2022)
In the relatively new but fast-evolving field of nanomedicine and nanotransport systems, different nanoscale molecules are used to deliver therapeutic agents to precisely targeted sites or potentially function as diagnostic tools. In present review provides up-to-date accurate information on the latest advancements in nanomedicine and nanotechnology DDS through a complete review of nanomaterials discoveries. The potential and difficulties of using nanomedicine to deliver medications from synthetic or natural sources to their intended clinical purposes are also covered. Additionally, we have exclusive data on perspectives and trends in nanomedicine.